The Effect of the Application of the Inquiry Learning Model on Students' Critical Thinking Skills in Subjects Pancasila Education Class IV SDN 20 Palu - Raehan Raehan; Arif Firmansyah; Muchdar; Herlina; Muhammad Nazimuddin Al Kamil (JED (Jurnal Etika Demokrasi), 2026)
This study aims to determine the effect of the application of the inquiry learning model on students' critical thinking skills in the subject of Pancasila Education grade IV SD Negeri 20 Palu. This study uses a quantitative approach with a pre-experimental method through a one-group pretest-posttest design. The research sample amounted to 26 grade IV students who were selected using the saturated sample technique. The data collection technique was carried out through pretest and posttest description tests as well as documentation. The research instrument was first tested for validity and reliability using the help of the SPSS version 25 program. The results of the reliability test showed a Cronbach's Alpha value of 0.811 which was in the high category. Data analysis was carried out through the Shapiro-Wilk normality test and hypothesis test using the Wilcoxon Signed-Rank Test because the data were not normally distributed. The results of the study showed that the average student pretest score of 23.26 increased to 67.11 in the posttest. The results of the Wilcoxon test obtained a significance value of 0.000 < 0.05 so that H₀ was rejected and Hₐ was accepted. Thus, it can be concluded that the application of the inquiry learning model has a significant effect on students' critical thinking skills in the Pancasila Education subject grade IV SD Negeri 20 Palu. The inquiry learning model is able to create active, exploratory learning, and encourages students to think critically through independent investigation, discussion, analysis, and conclusion drawing activities